Microworlds with Different Pedagogical Approaches in Introductory Programming Learning: Effects in Programming Knowledge and Logical Reasoning - Costa, Joana Martinho (Informatica (Ljubljana), 2019)
This paper presents a summary of doctoral thesis that evaluates the using of Alice microworld combined with different pedagogical approaches to learn introductory programming, specifically in programming knowledge and logical reasoning variables. The results suggest that when microworlds are combined with the 4C-ID instructional model there are positive effects in learning to program a computer, but they have no impact if an expository method is used. However, given the limited number of sampled subjects in this thesis, this topic should be further researched. It is necessary to understand to what extent, measurable, the use of certain teaching methods with or without association with microworlds, influence the results of students in knowledge and logical reasoning.